No need for a monetary halfway house: Lessons from the European Payments Union for post-Soviet currency arrangements - Holger Schmieding (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
The Soviet ruble has become the common currency for 14 independent states with their own policies on credit expansion and budget deficits. The built-in inflationary bias of the present arrangement can be redressed if the common ruble makes way for separate currencies. However, if major successor states of the Soviet Union switch to their own monies, trade between the former Soviet republics may be further disrupted as long as the new currencies are not convertible for current transactions. The European Payments Union (EPU) of the 1950s is often presented as a model for the successor states of the Soviet Union with separate currencies. However, the EPU clearing mechanism and its facility for soft credits were mere second-best devices to mitigate the harm that was caused by the inconvertibility and the collective overvaluation of the West European currencies against the dollar. In the 1950s, a sufficient devaluation of West European currencies would have removed the rationale for restrictions on trade and payments and would thus have made the EPU obsolete. Today, the former Soviet republics need not waste their time in a payments union, i.e. in a halfway house on the road to convertibility, unless they opted for a gross overvaluation of their currencies. In recent years, Poland, Hungary and Czechoslovakia have made their currencies convertible at least for most current transactions of their residents. This minimum convertibility has promoted their integration into the worldwide division of labour; it has been maintained because exchange rate policy has not led to a sustained misalignment. Instead of copying Western Europe's post-war mistake, the post-Soviet republics should follow the example of the East-Central European countries and make their currencies convertible at realistic and sufficiently flexible exchange rates. Regardless of their currency arrangements, the successor states of the Soviet Union have to transform their banking systems and establish an efficient system to clear payments between banks. Technical help from abroad could promote this process. However, the states need no mechanism that discriminates between interstate payments and payments between the states and third countries. Proponents of a special post-Soviet payments arrangement sometimes argue that such an institution would promote the cooperation between the successor states of the Soviet Union; it would thus be politically useful regardless of economic considerations. However, the strained political relations between many post-Soviet countries suggest that the readiness for a reliable cooperation is limited. Hence, special arrangements that inflate rather than economize on the need for cooperation are likely to be unstable.
Keywords: 330; Währungsunion; Devisenkontrolle; GUS-Staaten